Tantangan dan Evaluasi dalam Implementasi Kurikulum Merdeka Pada Sekolah di Kota Palangka Raya: Challenges and Evaluation in Implementing the Independent Curriculum in Schools in Palangka Raya City - Nanik Lestariningsih; Mukhlis Rohmadi (ITScience (Information Technology and Science), 2025)
Government policy in education is implemented by implementing an independent curriculum at all school levels. How prepared schools are to implement the independent curriculum needs to be known in terms of readiness, implementation, challenges and the future of the implementation in elementary and secondary schools in Palangka Raya. The objectives of this study include (1) challenges in implementation, (2) describing the implementation of the independent curriculum in schools, and (3) evaluation after the implementation of the independent curriculum. The method used in this study was a survey and needs assessment. The sample used was random sampling to 25 schools. The results of the study found that the challenges faced were socialization and training only online, so at the beginning of the implementation, they still did not understand, but continued to implement the independent curriculum while studying, preparing intracurricular and co-curricular lesson schedules, preparing formations in classes and cross-interest subjects with existing teacher human resources so that they are evenly distributed, compiling CP and teaching modules, because, in the previous curriculum, there were KI and KD teachers only reduced them to indicators and learning objectives, implementing the Pancasila student profile, independent curriculum teaching materials were not yet available, and administration in compiling the Operational Curriculum of Education Units (KOSP) or Madrasah Operational Curriculum (KOM). The implementation of the independent curriculum has 25 schools that have carried out the independent learning stage, 22 schools have been at the independent change stage, and 10 schools are at the independent sharing stage. 88.9% of teachers stated that the biggest challenge is the difference in learning components between the independent curriculum and the previous curriculum. Evaluation from teachers showed that 77.8% of the implementation of the independent curriculum improved students' hard and soft skills.